Negative regulation of miR‐1275 by H3K27me3 is critical for glial induction of glioblastoma cells. Issue 7 (18th June 2019) - Mai, Jialuo; Gu, Jiayu; Liu, Ying; Liu, Xincheng; Sai, Ke; Chen, Zhijie; Lu, Wanjun; Yang, Xiaozhi; Wang, Jingyi; Guo, Cui; Sun, Shuxin; Xing, Fan; et al.
Abstract : Activation of the cyclic adenosine monophosphate/protein kinase A (cAMP/PKA) pathway induces glial differentiation of glioblastoma (GBM) cells, but the mechanism by which microRNA (miRNA) regulate this process remains poorly understood. In this study, by performing miRNA genomics and loss‐ and gain‐of‐function assays in dibutyryl‐cAMP‐treated GBM cells, we identified a critical negative regulator, hsa‐miR‐1275, that modulates a set of genes involved in cancer progression, stem cell maintenance, and cell maturation and differentiation. Additionally, we confirmed that miR‐1275 directly and negatively regulates the protein expression of glial fibrillary acidic protein (GFAP), a marker of mature astrocytes. Of note, tri‐methyl‐histone H3 (Lys27) (H3K27me3), downstream of the PKA/polycomb repressive complex 2 (PRC2) pathway, accounts for the downregulation of miR‐1275. Furthermore, decreased miR‐1275 expression and induction of GFAP expression were also observed in dibutyryl‐cAMP‐treated primary cultured GBM cells. In a patient‐derived glioma stem cell tumor model, a cAMP elevator and an inhibitor of H3K27me3 methyltransferase inhibited tumor growth, induced differentiation, and reduced expression of miR‐1275. In summary, our study shows that epigenetic inhibition of miR‐1275 by the cAMP/PKA/PRC2/H3K27me3 pathway mediates glial induction of GBM cells, providing a new mechanism and novel targets for differentiation‐inducing therapy. Abstract : Mai et al. show that hsa‐miR‐1275 modulates glioblastoma (GBM) cells differentiation and transcriptionally constrains the expression of glial fibrillary acidic protein. Mechanistically, the cyclic adenosine monophosphate/protein kinase A (cAMP/PKA)/polycomb repressive complex 2/tri‐methyl‐histone H3 (Lys27) signal pathway mediates downregulation of miR‐1275, which leads to glial induction of GBM cells.